Fluorine-free synthesis of ambient-stable delaminated Ti2CTx (MXene). Issue 14 (10th March 2022) - Xue, Ni; Li, Xuesong; Han, Liuyuan; Zhu, He; Zhao, Xiangyan; Zhuang, Ji; Gao, Zeliang; Tao, Xutang
Abstract : The delaminated O-Ti2 CT x aqueous solution can be stably stored for 30 days, which is much higher than that of HCl- and LiF-etched Ti2 CT x (F-Ti2 C) (completely oxidized within 24 hours). Abstract : Compared with the widely used star material Ti3 C2 T x, Ti2 CT x, as a representative of thin layer MXenes, has unique and attractive performance in many fields, yet its development is severely hampered by its poor environmental instability. The nature of MXenes is closely related to the terminal groups, where the stability is no exception. Understanding the effect of different terminal groups on the stability of MXenes is of great significance to fundamentally improve the stability of MXenes. Herein, both experiment and theory results proved that compared with F terminal, the surface of Ti has higher oxidation state after bonding with O groups; thus, O terminal MXenes have better stability. Futhermore, a simplified and effective method to prepare fluorine-free Ti2 CT x with oxygen-rich terminals (O-Ti2 C) is proposed, which greatly improves the stability of delaminated Ti2 C aqueous solution. The delaminated O-Ti2 C aqueous solution can be stably stored for 30 days, much longer than that of HCl and LiF etched F-terminated Ti2 C (F-Ti2 C) (completely oxidized within 24 h). Furthermore, O-Ti2 C as a humidity sensor shows excellent performance with high response and good repeatability. This work greatly prolongs the shelf life of the Ti2 CT x solution, which will lay the foundation for the large-scale application and performance improvement of O-Ti2 C MXenes.